Rosa x hybrida extracts with dual actions: Antiproliferative effects against tumour cells and inhibitor of Alzheimer disease. (March 2021) - Rivas-García, Lorenzo; Quiles, José L.; Roma-Rodrigues, Catarina; Raposo, Luis R.; Navarro-Hortal, María D.; Romero-Márquez, Jose M.; Esteban-Muñoz, Adelaida; Varela-López, Alfonso; García, Laura Carrera; Cianciosi, Danila; Forbes Hernández, Tamara Y.; Battino, Maurizio; et al.
Abstract: Edible flowers are being used as a new ingredient in modern gastronomy. Recently, these products have also gained interest as an important source of phenolic compounds with potential for biomedical applications. The present work studied a methanolic extract of Rosa x hybrida in which 35 individual phenolic compounds were identified. The extract has been evaluated for its antiproliferative properties in ovarian carcinoma cells. Results showed that the antiproliferative effect was associated with the induction of autophagy and apoptosis with the concomitant ROS increase probably related to mitochondria dysfunction. These antiproliferative effects might be associated with some components of the extract such as quercetin. The extract did not induce damage in healthy cells and that it was able to improve the wound healing activity. The present study also evaluated the properties of the mentioned extract in vivo in C. elegans . Tests demonstrated a lack of toxicity in the worm model. Promising results have been obtained in transgenic strains of C. elegans that produce human beta amyloid peptide, suggesting the possible utility of the extract from the point of view of Alzheimer disease. Altogether, results suggest that Rosa x hybrida extracts could be a new tool for the development of functional foods. Graphical abstract: Image 1 Highlights: Rosa x hybrida extract inhibited the growth of ovarian tumoral cell lines. The antitumoral effect was mediated by induction of autophagy and ROS production. Petals extract was not toxic for fibroblasts and worms. The extract might be useful for beta-amyloid reduction in Alzheimer disease.